Mi lengua materna y yo - Perry Price, Franklyn (2013)
This article presents a reflection of Limonese Creole and how speakers of other languages haveperceived its use in domains of usage like the academic classroom. In addition, considering thepossible disappearance of Limonese Creole, the author enumerates arguments to the contrary, forexample, the ongoing linguistic study of this language, its daily use in differing contexts by itsspeakers, employment and, maybe the most important, that fact that it is used in other places andnot solely in Limon.